2015
DOI: 10.1111/jgh.12791
|View full text |Cite
|
Sign up to set email alerts
|

Radiofrequency ablation versus laser ablation for the treatment of small hepatocellular carcinoma in cirrhosis: A randomized trial

Abstract: LA resulted not inferior to RFA in inducing the CTA of HCC nodules and therefore it should be considered as an evaluable alternative for thermal ablation of small HCC in cirrhotic patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(47 citation statements)
references
References 44 publications
2
43
0
2
Order By: Relevance
“…Three RCTs were included in this assessment [7, 34, 35]. A fixed-effect model revealed no significant difference in tumor diameter (mean difference 0.11, 95% CI −0.08 to 0.30) between the LSA and RFA groups.…”
Section: Resultsmentioning
confidence: 99%
“…Three RCTs were included in this assessment [7, 34, 35]. A fixed-effect model revealed no significant difference in tumor diameter (mean difference 0.11, 95% CI −0.08 to 0.30) between the LSA and RFA groups.…”
Section: Resultsmentioning
confidence: 99%
“…In a recent RCT with 140 Milan-in patients, complete response was observed in 97.4% of patients treated with RFA and 95.7% with LA and mean time-to local progression and overall survival were comparable between the two study groups ( P = 0.129 and 0.693, respectively)[110]. The authors concluded that LA resulted non-inferior to RFA and therefore it should be considered as a valuable alternative for thermal ablation of small HCC in cirrhotic patients[110].…”
Section: Other Thermal Ablation Techniquesmentioning
confidence: 99%
“…The authors concluded that LA resulted non-inferior to RFA and therefore it should be considered as a valuable alternative for thermal ablation of small HCC in cirrhotic patients[110]. …”
Section: Other Thermal Ablation Techniquesmentioning
confidence: 99%
“…The adventages of the small needle and precise thermal energy distribution theoretically could minimize the risk of off-target burning and decrease problems in treating lymph nodes and particularly in difficult anatomical location. Previous studies have focused on laser ablation in the prostate [14, 15], thyroid [1619] and liver [20, 21] while the present study aimed to assess the safety and efficacy of ultrasonography (US)-guided local Nd:YAG laser ablation for metastatic lymph nodes in the retroperitoneal region. Additionally, we performed a systematic review of the literature.…”
Section: Introductionmentioning
confidence: 99%